Effect of Marine and Vegetal Sources on the Hen Diets on the PUFAs and PUFAs n-3 in Laying Hens Egg Yolk and Plasm - Pita, Maria Carolina G.; Carvalho, Paulo R.; Neto, Eduardo Piber; Junior, Cassio Xavier de Mendonca (International Journal of Poultry Science, 2010)
The present study was aimed to verify the effect of 3% oil addition (soil, corn, canola, linseed, salmon or sardine tuna) chicken diets on the yolk and plasmatic fatty acids composition. 144 Shaver White poultry were housed during four weeks. The inclusion of linseed, soil or corn oil on the diet increased the polyunsaturated fatty acids in yolk and plasm. Linseed oil treatment promoted higher levels of yolk and plasm PUFAs n-3. The EPA and DHA concentration in the plasm were higher in 3% sardine tuna oil and DHA plasm value was increased in both group received fish oils. The plasm fatty acid profile was similar to that found in egg yolk.